Enhancing perceptual and attentional skills requires common demands between the action video games and transfer tasks - Oei, Adam C.; Patterson, Michael D. (Frontiers in Psychology, 2015)
Despite increasing evidence that shows action video game play improves perceptual and cognitive skills, the mechanisms of transfer are not well understood. In line with previous work, we suggest that transfer is dependent upon common demands between the game and transfer task. In the current study, participants played one of four action games with varying speed, visual, and attentional demands for twenty hours. We examined whether training enhanced performance for attentional blink, selective attention, attending to multiple items, visual search and auditory detection. Non-gamers who played the game (Modern Combat) with the highest demands showed transfer to tasks of attentional blink and attending to multiple items. The game (MGS Touch) with fewer attentional demands also decreased attentional blink, but to a lesser degree. Other games failed to show transfer, despite having many action game characteristics but at a reduced intensity. The results support the common demands hypothesis